Lithium ion battery diaphragm slurry and preparation method thereof, lithium ion battery composite diaphragm
By using functional coating prepared by composite adsorption material powder on the lithium-ion battery separator, the problem of transition metal ion dissolution in lithium-ion batteries is solved, the cycle performance and safety performance of the battery are improved, and the thermal shrinkage rate is reduced.
Patent Information
- Application Number
- CN202210454182.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-04-27
AI Technical Summary
Lithium-ion batteries dissolve transition metal elements under high temperature or high voltage conditions, causing the electrolyte to decompose and produce HF, corrode the positive electrode material, destroy the SEI film, affecting the battery capacity and cycle life. Existing polyolefin or ceramic separators cannot effectively adsorb metal ions. .
The composite adsorbent material powder is prepared by solution polymerization by using composite adsorbent material powder, including non-metallic minerals such as concave and concave rock stone, acrylamide monomers and initiators, and the composite adsorbent material powder is combined with polyacrylamide and surfactant to form a lithium-ion battery separator. Coated onto the polyolefin-based film, a functional coating is formed to capture the dissolved heavy metal ions.
Effectively capture heavy metal ions inside the battery, reduce the precipitation of metal ions to destroy the SEI film or puncture the diaphragm, improve the battery circulation and safety performance, reduce heat shrinkage, and improve the thermal stability and conductivity of the diaphragm.
Smart Images

Figure CN114784451B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a lithium ion battery diaphragm slurry and a preparation method thereof, and a lithium ion battery composite diaphragm. Background Art
[0002] With the continuous development of science and technology and the progress of society, the energy crisis has gradually deepened, people's environmental awareness has continued to increase, and the new energy and environmentally friendly low-carbon electric vehicle industries have developed rapidly. Lithium-ion batteries have long cycle life and high energy ratio, and are rechargeable and pollution-free. They stand out among many types of batteries and have become one of the key technologies to solve the low-carbon, clean and efficient energy system.
[0003] During the use of lithium-ion batteries, transition metal elements will dissolve. Especially when charging and discharging at high temperature or high voltage, the electrolyte of lithium-ion batteries is easy to decompose and produce HF. HF will corrode the positive electrode material, causing the positive electrode material to dissolve transition metal ions Ni, Mn, and Co. The dissolved transition metal elements will migrate to the surface of the negative electrode, destroy the SEI film or precipitate, resulting in irreversible decline in battery capacity, or pierce the battery diaphragm, affecting the capacity, cycle life and self-discharge performance of the lithium-ion battery. The composite diaphragm of the lithium-ion battery is located between the positive and negative electrodes of the lithium-ion battery. It is an electronic insulator that allows ions to migrate freely to achieve reversible "embedding" and "de-embedding" reactions. Therefore, from the perspective of diaphragm design, fully adsorbing the transition metal ions dissolved inside the lithium-ion battery has become an effective means to improve the battery cycle performance and safety performance. At present, commercial lithium-ion batteries are still mainly polyolefin diaphragms or ceramic diaphragms, which cannot effectively adsorb metal ions. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a lithium ion battery diaphragm slurry and a preparation method thereof, and a lithium ion battery composite diaphragm.
[0005] A lithium ion battery separator slurry disclosed in the present invention comprises:
[0006] Composite adsorption material powder, dispersant, deionized water, binder and surfactant, the weight ratio of the composite adsorption material powder, dispersant, deionized water, binder and surfactant is 1:0.001-0.005:2.9-6.8:0.1-0.4:0.004-0.007;
[0007] The composite adsorption material powder includes non-metallic minerals, acrylamide monomers, initiators and deionized water, and the mass ratio of the non-metallic minerals, acrylamide monomers, initiators and deionized water is 1:0.15-0.45:0.01-0.05:10-50.
[0008] According to one embodiment of the present invention, the non-metallic mineral is one or more of diatomite, zeolite, sepiolite, attapulgite and montmorillonite.
[0009] According to one embodiment of the present invention, the non-metallic mineral is attapulgite having a one-dimensional nanorod-like structure and an internally connected micro-nanopore structure, and the particle size thereof is 400 to 1000 nm.
[0010] According to one embodiment of the present invention, the initiator is azobisisobutyronitrile or potassium persulfate.
[0011] According to one embodiment of the present invention, the dispersant is one or more of sodium silicate, polyacrylic acid, sodium polyacrylate, sodium hexametaphosphate, ammonium polyacrylate, and sodium pyrophosphate.
[0012] According to one embodiment of the present invention, the binder is one or more of styrene acrylic latex, styrene butadiene rubber, polymethyl methacrylate, polybutyl methacrylate, polyvinyl pyrrolidone, polyethylene oxide, polyvinyl alcohol, and sodium carboxymethyl cellulose.
[0013] According to one embodiment of the present invention, the surfactant is polyoxyethylene fatty alcohol ether.
[0014] A method for preparing a lithium-ion battery composite diaphragm coating slurry comprises the following steps:
[0015] (1) Preparing composite adsorption material powder by solution polymerization;
[0016] (2) Weighing the adsorption material powder, dispersant, deionized water, binder and surfactant, mixing the adsorption material powder, dispersant and deionized water evenly, adding the binder and surfactant, and stirring evenly to form a lithium-ion battery composite diaphragm coating slurry.
[0017] According to one embodiment of the present invention, step (1) comprises:
[0018] Weigh non-metallic minerals, acrylamide monomer, initiator and deionized water, add them into a reaction bottle, ultrasonically disperse for 30 minutes, then add the initiator, place the reaction bottle in a water bath under nitrogen protection for constant temperature polymerization, after the polymerization is completed, wash the product with deionized water, dry it, grind and sieve it to obtain the composite adsorption material powder.
[0019] A lithium ion battery composite diaphragm is obtained by transferring the lithium ion battery diaphragm slurry to one side or both sides of a polyolefin base film by dipping, rotary spraying, roller coating or template printing, and drying the diaphragm.
[0020] The beneficial effects of the present application are: using polyacrylamide / non-metallic mineral composite material as the functional coating of the lithium-ion battery composite diaphragm, the prepared composite coated diaphragm can effectively capture the heavy metal ions dissolved from the battery, reduce the precipitation of metal ions at the negative electrode to damage the SEI film or puncture the diaphragm, and improve the battery cycle performance and safety performance; and the polyacrylamide / non-metallic mineral coating has a good supporting effect on the lithium-ion battery composite diaphragm, reduces the degree of shrinkage of the diaphragm when heated, and improves the thermal shrinkage performance of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0022] Figure 1 The Mn content of the negative electrode sheets of Examples 1 to 3 and the comparative example is 500 cycles. DETAILED DESCRIPTION
[0023] The following will disclose a number of embodiments of the present invention. For the purpose of clarity, many practical details will be described together in the following description. However, it should be understood that these practical details should not be used to limit the present invention. That is, in some embodiments of the present invention, these practical details are not necessary.
[0024] A lithium ion battery composite diaphragm coating slurry comprises composite adsorption material powder, dispersant, deionized water, binder and surfactant, wherein the weight ratio of the composite adsorption material powder, dispersant, deionized water, binder and surfactant is 1:0.001-0.005:2.9-6.8:0.1-0.4:0.004-0.007.
[0025] Among them, the composite adsorption material powder includes non-metallic minerals, acrylamide monomers, initiators and deionized water, and the mass ratio between non-metallic minerals, acrylamide monomers, initiators and deionized water is 1:0.15~0.45:0.01~0.05:10~50. Preferably, the non-metallic mineral is one or more of diatomite, zeolite, sepiolite, attapulgite and montmorillonite. Further, the non-metallic mineral is attapulgite with a one-dimensional nanorod structure and an internally connected micro-nanopore structure, and its particle size is 400~1000nm. There are a large number of hydrophilic silanol groups on the surface of attapulgite, which have good affinity for electrolytes and can improve the liquid absorption performance of the diaphragm. Attapulgite mainly adsorbs metal ions through physical adsorption and ion exchange adsorption. By grafting the strongly polar amide groups on polyacrylamide to the surface of attapulgite, the synergistic adsorption effect of polyacrylamide and attapulgite is utilized to further improve the adsorption capacity of polyacrylamide. Moreover, the affinity between attapulgite and polyolefin separator is poor. The compatibility of attapulgite and polyolefin separator can be enhanced by compounding with polyacrylamide, thereby reducing the occurrence of leakage coating.
[0026] Preferably, the initiator is azobisisobutyronitrile or potassium persulfate. The dispersant is one or more of sodium silicate, polyacrylic acid, sodium polyacrylate, sodium hexametaphosphate, ammonium polyacrylate, and sodium pyrophosphate. The binder is one or more of styrene-acrylic latex, styrene-butadiene rubber, polymethyl methacrylate, polybutyl methacrylate, polyvinyl pyrrolidone, polyethylene oxide, polyvinyl alcohol, and sodium carboxymethyl cellulose. The surfactant is polyoxyethylene fatty alcohol ether.
[0027] A method for preparing a lithium-ion battery composite diaphragm coating slurry comprises the following steps:
[0028] (1) Preparing composite adsorption material powder by solution polymerization;
[0029] (2) Weigh the adsorption material powder, dispersant, deionized water, binder and surfactant, mix the adsorption material powder, dispersant and deionized water for 30 minutes, add the binder and surfactant and stir for 60 minutes at a speed of 400 to 800 rpm to form a lithium-ion battery composite diaphragm coating slurry.
[0030] Preferably, step (1) comprises:
[0031] Weigh non-metallic minerals, acrylamide monomer, initiator and deionized water, add non-metallic minerals, acrylamide monomer and deionized water into a reaction bottle, ultrasonically disperse for 30 minutes, then add the initiator, place the reaction bottle in a water bath under nitrogen protection at 80°C for constant temperature polymerization, react for 5 hours, after the polymerization is completed, wash the product with deionized water, dry it at 100°C, grind and sieve to obtain composite adsorption material powder.
[0032] A lithium-ion battery composite diaphragm, characterized in that the lithium-ion battery diaphragm slurry is transferred to one side or both sides of a polyolefin base film by dipping, rotary spraying, roller coating or template printing, and then dried to obtain the composite diaphragm.
[0033] Preferably, the polyolefin-based film is a polyethylene-based film or a polypropylene-based film, the drying temperature is 50-65° C., and the coating thickness is 1-4 μm.
[0034] Polyacrylamide / non-metallic mineral composite material is used as the functional coating of the lithium-ion battery composite diaphragm. The prepared composite coated diaphragm can effectively capture the heavy metal ions dissolved from the battery, reduce the precipitation of metal ions at the negative electrode to damage the SEI film or puncture the diaphragm, and improve the battery cycle performance and safety performance; and the polyacrylamide / non-metallic mineral coating has a good supporting effect on the lithium-ion battery composite diaphragm, reduces the degree of shrinkage of the diaphragm when heated, and improves the thermal shrinkage performance of the diaphragm.
[0035] In order to further understand the content, features and effects of the present invention, the following embodiments are given as examples and described in detail with reference to the accompanying drawings:
[0036] Embodiment 1:
[0037] The attapulgite powder (D50 = 600nm), acrylamide monomer, azobisisobutyronitrile and deionized water were weighed in a mass ratio of 1:0.25:0.02:20, and the attapulgite powder, acrylamide monomer and deionized water were added to a reaction bottle, ultrasonically dispersed for 30 minutes, azobisisobutyronitrile was added, and the mixture was placed in a water bath under nitrogen protection at 80°C for constant temperature polymerization. The reaction was performed for 5 hours. After the polymerization was completed, the product was washed with deionized water, dried at 100°C, and ground and sieved to obtain a composite adsorption material powder.
[0038] The composite adsorbent material powder, sodium hexametaphosphate, deionized water, polymethyl methacrylate and polyoxyethylene fatty alcohol ether were weighed in a mass ratio of 1:0.003:4.38:0.3:0.005, and the composite adsorbent material powder, sodium hexametaphosphate and deionized water were added into a reaction bottle. After stirring for 30 minutes, polymethyl methacrylate and polyoxyethylene fatty alcohol ether were added, and stirred for 60 minutes using a high-speed disperser at a stirring speed of 450 rpm to form a lithium-ion battery composite diaphragm coating slurry with a solid content of 30%.
[0039] The lithium-ion battery composite diaphragm coating slurry was evenly coated on the PE base film by gravure coating. The base film thickness was 12μm and the coating thickness was 4μm. The coating film was dried at 60°C to obtain the lithium-ion battery composite diaphragm. The lithium-ion battery composite diaphragm was immersed in the lithium-ion battery electrolyte (1M LiPF6EC / DMC). Its liquid absorption rate was 230%. The lithium-ion battery composite diaphragm was tested for moisture in the glove box with a Karl Fischer titrator. Its water content was 670ppm. The thermal shrinkage value MD of the lithium-ion battery composite diaphragm at 130°C / 1h was 2.11%, and TD was 1.34%. The ionic conductivity of the lithium-ion battery composite diaphragm is 1.66 mS / cm The lithium manganese oxide positive electrode material, graphite, electrolyte and lithium ion battery composite separator were assembled into a battery and its performance was tested. The capacity retention rate was 90.72% after 500 charge and discharge cycles at room temperature at 1C rate, and the capacity retention rate was 85.56% after 500 charge and discharge cycles at 55℃ at 1C rate. The Mn ion content of the negative electrode sheet after room temperature cycling was 225ppm, and the Mn ion content of the negative electrode sheet after 55℃ cycling was 293ppm.
[0040] Embodiment 2:
[0041] The attapulgite powder (D50 = 600nm), acrylamide monomer, azobisisobutyronitrile and deionized water were weighed in a mass ratio of 1:0.4:0.02:20, added into a reaction bottle, ultrasonically dispersed for 30 minutes, added with azobisisobutyronitrile, and placed in a water bath under nitrogen protection at 80°C for constant temperature polymerization for 5 hours. After the polymerization was completed, the product was washed with deionized water, dried at 100°C, and ground and sieved to obtain a composite adsorption material powder.
[0042] The composite adsorbent material powder, sodium hexametaphosphate, deionized water, polymethyl methacrylate and polyoxyethylene fatty alcohol ether were weighed in a mass ratio of 1:0.003:4.38:0.3:0.005, and the composite adsorbent material powder, sodium hexametaphosphate and deionized water were added into a reaction bottle. After stirring for 30 minutes, polymethyl methacrylate and polyoxyethylene fatty alcohol ether were added, and stirred for 60 minutes using a high-speed disperser at a stirring speed of 450 rpm to form a lithium-ion battery composite diaphragm coating slurry with a solid content of 30%.
[0043] The lithium-ion battery composite diaphragm coating slurry was evenly coated on the PE base film by gravure coating. The base film thickness was 12μm and the coating thickness was 4μm. The coating film was dried at 60°C to obtain the lithium-ion battery composite diaphragm. The lithium-ion battery composite diaphragm was immersed in the lithium-ion battery electrolyte (1M LiPF6EC / DMC), and its liquid absorption rate was 204%. The lithium-ion battery composite diaphragm was tested for moisture in the glove box with a Karl Fischer titrator, and its water content was 620ppm; the thermal shrinkage value MD of the lithium-ion battery composite diaphragm at 130°C / 1h was 3.60%, and TD was 3.21%. The ionic conductivity of the lithium-ion battery composite diaphragm is 1.11 mS / cm The lithium manganese oxide positive electrode material, graphite, electrolyte and lithium ion battery composite separator were assembled into a battery and its performance was tested. The capacity retention rate was 87.58% after 500 charge and discharge cycles at room temperature at 1C rate, and the capacity retention rate was 80.37% after 500 charge and discharge cycles at 55℃ at 1C rate. The Mn ion content of the negative electrode sheet after room temperature cycling was 273ppm, and the Mn ion content of the negative electrode sheet after 55℃ cycling was 385ppm.
[0044] Embodiment 3:
[0045] The attapulgite powder (D50 = 1100 nm), acrylamide monomer, azobisisobutyronitrile and deionized water were weighed in a mass ratio of 1:0.25:0.02:20, added into a reaction bottle, ultrasonically dispersed for 30 min, azobisisobutyronitrile was added, and the mixture was placed in a water bath under nitrogen protection at 80 ° C for constant temperature polymerization, and the reaction was carried out for 5 h. After the polymerization was completed, the product was washed with deionized water, dried at 100 ° C, and ground and sieved to obtain a composite adsorption material powder.
[0046] The composite adsorbent material powder, sodium hexametaphosphate, deionized water, polymethyl methacrylate and polyoxyethylene fatty alcohol ether were weighed in a mass ratio of 1:0.003:4.38:0.3:0.005, and the composite adsorbent material powder, sodium hexametaphosphate and deionized water were added into a reaction bottle. After stirring for 30 minutes, polymethyl methacrylate and polyoxyethylene fatty alcohol ether were added, and stirred for 60 minutes using a high-speed disperser at a stirring speed of 450 rpm to form a lithium-ion battery composite diaphragm coating slurry with a solid content of 30%.
[0047] The lithium-ion battery composite diaphragm coating slurry was evenly coated on the PE base film by gravure coating. The base film thickness was 12μm and the coating thickness was 4μm. The coating film was dried at 60°C to obtain the lithium-ion battery composite diaphragm. The lithium-ion battery composite diaphragm was immersed in the lithium-ion battery electrolyte (1M LiPF6 EC / DMC). Its liquid absorption rate was 191%. The lithium-ion battery composite diaphragm was tested for moisture in the glove box with a Karl Fischer titrator. Its water content was 518ppm. The thermal shrinkage value of the lithium-ion battery composite diaphragm at 130°C / 1h was 3.25% MD and 2.83% TD. Its ionic conductivity was 1.78 mS / cm . The lithium manganese oxide positive electrode material, graphite, electrolyte and lithium ion battery composite diaphragm were assembled into a battery and its performance was tested. The capacity retention rate was 88.68% after 500 charge and discharge cycles at room temperature at a rate of 1C, and the capacity retention rate was 82.51% after 500 charge and discharge cycles at 55°C at a rate of 1C. The Mn ion content of the negative electrode plate after normal temperature cycling was 258ppm, and the Mn ion content of the negative electrode plate after 55°C cycling was 325ppm. The performance test results of the composite diaphragm prepared by the method described in Examples 1 to 3 and the comparative example (ceramic diaphragm 12+4C) are shown in Tables 1 and Figure 1 As shown in Table 1, the performance test results of the membranes of Examples 1 to 3 and the comparative example are shown. Figure 1 The Mn content of the negative electrode sheets of Examples 1 to 3 and the comparative example is 500 cycles.
[0048] Table 1 Performance test results of examples 1 to 3 and comparative example diaphragms
[0049]
[0050] From the experimental results, it can be seen that compared with the comparative example, the lithium ion battery composite diaphragm in Examples 1 to 3 has a higher liquid absorption rate, lower water content, better conductivity ions, and better battery capacity retention at room temperature and 55°C, which improves the battery's cycle performance and safety performance. At the same time, the Mn content of the negative electrode sheet is greatly reduced, indicating that the lithium ion battery composite diaphragm in Examples 1 to 3 can effectively capture the heavy metal ions dissolved from the battery, reduce the precipitation of metal ions at the negative electrode to damage the SEI film or puncture the diaphragm. And the thermal shrinkage rate of the lithium ion battery composite diaphragm in Example 1 is less than the thermal shrinkage rate of the lithium ion battery diaphragm in the comparative example, which improves the thermal shrinkage performance of the diaphragm.
[0051] In summary: the lithium-ion battery composite diaphragm in the present application adopts polyacrylamide / non-metallic mineral composite material as the functional coating of the lithium-ion battery composite diaphragm, and the prepared composite coated diaphragm can effectively capture the heavy metal ions dissolved from the battery, reduce the precipitation of metal ions at the negative electrode to damage the SEI film or puncture the diaphragm, and improve the battery cycle performance and safety performance; and the polyacrylamide / non-metallic mineral coating has a good supporting effect on the lithium-ion battery composite diaphragm, reduces the degree of shrinkage of the diaphragm when heated, and improves the thermal shrinkage performance of the diaphragm.
[0052] The above is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A lithium-ion battery composite diaphragm coating slurry, characterized in that: include: Composite adsorption material powder, dispersant, deionized water, binder and surfactant, wherein the weight ratio of the composite adsorption material powder, dispersant, deionized water, binder and surfactant is 1:0.001-0.005:2.9-6.8:0.1-0.4:0.004-0.007; The composite adsorption material powder includes non-metallic minerals, acrylamide monomers, initiators and deionized water, and the mass ratio of the non-metallic minerals, acrylamide monomers, initiators and deionized water is 1:0.15-0.45:0.01-0.05:10-50; The non-metallic mineral is attapulgite having a one-dimensional nanorod structure and an internally connected micro-nanopore structure, and its particle size is 400 to 1000 nm; The initiator is azobisisobutyronitrile or potassium persulfate; The dispersant is one or more of sodium silicate, polyacrylic acid, sodium polyacrylate, sodium hexametaphosphate, ammonium polyacrylate, and sodium pyrophosphate; The binder is one or more of styrene acrylic latex, styrene butadiene rubber, polymethyl methacrylate, polybutyl methacrylate, polyvinyl pyrrolidone, polyethylene oxide, polyvinyl alcohol, and sodium carboxymethyl cellulose; The surfactant is polyoxyethylene fatty alcohol ether.
2. The method for preparing a lithium-ion battery composite diaphragm coating slurry according to claim 1, characterized in that: The following steps are involved: (1) Preparing composite adsorption material powder by solution polymerization; (2) Weighing the adsorbent material powder, dispersant, deionized water, binder and surfactant, mixing the adsorbent material powder, dispersant and deionized water and stirring them evenly, adding the binder and surfactant, and stirring evenly to form a lithium ion battery composite diaphragm coating slurry.
3. The method for preparing a lithium-ion battery composite diaphragm coating slurry according to claim 2, characterized in that: The step (1) comprises: The non-metallic mineral, acrylamide monomer, initiator and deionized water are weighed, added into a reaction bottle, ultrasonically dispersed for 30 minutes, and then the initiator is added. The reaction bottle is placed in a water bath for constant temperature polymerization under nitrogen protection. After the polymerization is completed, the product is washed with deionized water, dried, ground and sieved to obtain a composite adsorption material powder.
4. A lithium-ion battery composite diaphragm, characterized in that: The lithium-ion battery composite membrane is prepared by transferring the lithium-ion battery membrane slurry according to claim 1 to one side or both sides of a polyolefin base film by dipping, rotary spraying, roller coating or template printing, and then drying.
Citation Information
Patent Citations
Mixed slurry for preparing composite diaphragm and preparation method of composite diaphragm
CN107528038A
Modification method of attapulgite clay and modified attapulgite clay
CN111097366A
